1988
DOI: 10.1161/01.hyp.12.6.568
|View full text |Cite
|
Sign up to set email alerts
|

Failure of salt loading to inhibit tissue norepinephrine turnover in prehypertensive Dahl salt-sensitive rats.

Abstract: SUMMARY To determine if alterations of electrolyte balance or sympathetic nervous system activity are present in Dahl salt-sensitive rats (DS) before the onset of hypertension, we compared electrolyte balances, extracellular fluid volume (inulin space), plasma volume (radiolabeled albumin), and norepinephrine turnover in peripheral tissues (heart and interscapular brown fat) in prehypertensive DS and Dahl salt-resistant rats (DR). Animals were maintained for 5 to 7 days on either a "normal" or high NaCl diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
5
14
0
Order By: Relevance
“…The mean systolic pressure was slightly higher in the DS compared with the DR rats, both before initiation of salt diets and after 5 days on the diets. However, consistent with our previous experience, 9 systolic pressure in DS rats after 5 days on the 7% NaCl diet was not increased above that in DS rats on the normal salt diet.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The mean systolic pressure was slightly higher in the DS compared with the DR rats, both before initiation of salt diets and after 5 days on the diets. However, consistent with our previous experience, 9 systolic pressure in DS rats after 5 days on the 7% NaCl diet was not increased above that in DS rats on the normal salt diet.…”
Section: Resultssupporting
confidence: 92%
“…9 Thus, the differences in sensitivity observed could represent significant factors in the initiation of hypertension but are not secondary to elevated pressure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This discrepancy may be due to the use of anesthetized animals in these earlier reports. The results from the present experiments are consistent with investigations reporting that increases in dietary sodium are associated with diminished SNS drive in rats (3,13) and in humans (21,30).…”
Section: Discussionsupporting
confidence: 92%
“…We have previously reported that plasma volume is greater in Dahl salt-sensitive than in Dahl salt-resistant rats maintained on a "normal" NaCl diet. 17 Other investigators have also found either transient or sustained elevations of plasma volume in the Dahl salt-sensitive rat. 18 -20 Studies of selective sodium loading support the hypothesis that volume mechanisms contribute to the pathogenesis of salt-sensitive hypertension.…”
Section: Volume Mechanismsmentioning
confidence: 95%